Design and performance evaluation of edible film printing machine based on automatic casting knife. Issue 1 (April 2021) - Putranto, A W; Sakhbani, M M; Khoir, N H; Mutiarani, N; Susilo, B; Hermanto, M B
Abstract: The development of edible films has been widely applied in recent years as an environmentally friendly food packaging, increasing shelf life and improving food quality. The most commonly used technique for producing starch-based films was classical casting, leading to film thickness measurement difficult. Therefore, this study aimed to design an edible film printing machine based on an automatic casting knife. The method used in this research was the engineering method. The edible printing machine was designed for a laboratory scale with a 1200 mm length, 500 mm width and 300 mm height. There were three main parts, namely an automatic casting knife, automatic pouring and control box. The performance evaluation showed that the automatic casting knife could be printing an edible film thickness between 0-20 mm with an accuracy level of 99.3%. An edible film with a length of 200 mm and 130 mm width can be printed in a shorter time (10 seconds). The edible film also has a smoother appearance on microscopic observation and was preferred by panellists to its appearance, texture and transparency parameters compared with edible film from manual casting. Based on the performance evaluation results that promise to be more efficient in printing edible film, this machine was expected to be scaled up and become a solution for the realization of Indonesian green packaging in the industrial revolution 4.0.